Exploring Current Practice of Using Technology to Support Collaborative Argumentation in Science Classrooms - Pi-Sui Hsu; Saurav Mukhopadhyay; Rakez Al-Ararah (Middle Grades Review, 2020)
The purpose of this qualitative study was to explore how middle school science teachers enact the practice of using technology to support collaborative argumentation in their science classroom. This study employed qualitative case study and drew on data sources of interviews and observations. This study identified two themes. Six teachers regarded scientific argumentation as an important science practice, but five of them integrated this practice into their science class without formally introducing it. All teachers integrated different forms of technology to engage students in scientific argumentation. In this study, the findings suggested there is a need to provide professional development for teachers to learn about scientific argumentation. The findings can be used as a basis for the design and development of professional development training experiences for in-service
Keywords: scientific argumentation; middle schools; technology integration